ANALISIS KESALAHANBERBAHASA DALAM TUGASSAKUBUN - Zida Wahyuddin (Universitas 17 Agustus 1945 Surabaya, 2012)
Abstrak.The focus of this paper is to analyze errors or irregularities in the form of improper use of the Japanese grammar in sakubun task (essay writing) as a variety of written languages.This researchadopts error analysis method with sakubuntask transcript as the data sources.The results of this research indicate that the language errorsmay be caused by interference of the first language (LI) on the studentsâ€™ foreign language learning (L2).The study also shows that errors may be caused by lack of studentsâ€™mastery of the Japanese grammar.Â Kata kunci: language errors, grammar, sakubun